Kearifan Lokal “Mambongoti Bagas” dalam Suku Batak Toba di Pematang Siantar - Sitompul, Ferren Audy Febina; Dora, Nuriza (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
This research delves into the uniqueness of the local wisdom "Mambongoti Bagas" in the Toba Batak tribe in Pematang Siantar. The main focus of the research is to examine the essence, purpose, and implications of the practice of "Mambongoti Bagas" in the context of Toba Batak community life. This research aims is to explore the meaning and values contained in the practice of Mambongoti Bagas, as well as to understand its influence on traditional knowledge systems, patterns of community behavior, cultural heritage, and its important role in preserving and conserving the cultural identity of the Toba Batak tribe. The results of this research reveal that Mambongoti Bagas is a sacred place with deep symbolism. This sacred place symbolizes community unity, spirit of mutual cooperation, respect for ancestors, and awareness of environmental sustainability. In addition, Mambongoti Bagas also functions as a center for traditional learning where values such as respect, cooperation, and social care are instilled in the community. During the research, the transmission of this local wisdom from generation to generation was revealed through stories, oral teachings, and participation in traditional ceremonies. In conclusion, this research confirms the importance of preserving and conserving Mambongoti Bagas as a valuable asset in maintaining the sustainability of the cultural identity and local wisdom of the Toba Batak community.